The IVth International Conference on Quarks and Nuclear Physics
DOI: 10.1007/978-3-540-72516-9_126
|View full text |Cite
|
Sign up to set email alerts
|

Scenario of instabilities driven equilibration of the quark-gluon plasma

Abstract: Due to anisotropic momentum distributions the parton system produced at the early stage of relativistic heavy-ion collisions is unstable with respect to the magnetic plasma modes. The instabilities isotropize the system and thus speed up the process of its equilibration. The whole scenario of the instabilities driven isotropization is reviewed.1 The term 'parton' is used to denote a quasiparticle fermionic (quark) or bosonic (gluon) excitation of the quark-gluon plasma. 2 Although anisotropic systems are consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 86 publications
0
8
0
Order By: Relevance
“…According to Eqs. (31), (32), (33) and the introduced EoS, we can obtain the colored fluctuations of the particle density and the plasma speed (see details in Appendix B)…”
Section: The Polarization Tensor π μν and The Dielectric Function Lmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Eqs. (31), (32), (33) and the introduced EoS, we can obtain the colored fluctuations of the particle density and the plasma speed (see details in Appendix B)…”
Section: The Polarization Tensor π μν and The Dielectric Function Lmentioning
confidence: 99%
“…[31,32] which will isotropize the produced parton system in the heavy ion collisions and speed up the thermalization process (for reviews see [33,34]), which is helpful to understand the fast thermalization at RHIC. In the current work, by extending the ideal chromohydrodynamic equations [31,32] to the viscous ones, we investigate the effects of the shear viscosity on the dielectric function of the QGP.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been suggested that QCD perturbation theory, no matter at which order one truncates it, may be unable to describe thermalization at all [4]. Plasma instabilities, particularly the Weibel instability [5,6,7,8,9,10,11,12], could be promising candidates for the early thermalization mechanism [13] and have been well investigated in the hard-loop formalism [14,15,16,17,18]. There are also various other approaches [19,20,21,22] including a framework based on the AdS/CFT correspondence [23,24,25,26], in which thermalization appears as the formation of a black hole horizon in the dual theory.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, perturbative estimates of the thermalization time [2] result in much larger values, seemingly excluding the possibility of rapid thermalization (see however [3]) . Plasma instabilities may help speeding up the equilibration process by rapidly isotropizing the system [4,5,6,7,8], probably by some cascade to the UV [9,10,11,12,13], although they might still be too slow to overcome the initially strong longitudinal expansion rate [14]. Thus, it is currently unclear how (and if) the quark gluon plasma created at RHIC stays locally isotropic (let alone thermal) during most of its time evolution.…”
Section: Introductionmentioning
confidence: 99%